Training of Making Sheredded Banana Flower (Musa paradisiaca) in the Development of Local Food Products in Rantau Panjang Kiri Village Kubu Babussalam District Rokan Hilir - Mhd. Andry Kurniawan; Dewi Fortuna Ayu; Raswen Efendi; Ayu Diana; Erpiani Siregar; Imelda Yunita; Yossie Kharisma Dewi; Rahmadini Payla Juarsa (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Training of making shredded banana flower (Musa paradisiaca) is one of the efforts in developing local food products that have the potential to increase the economic value of banana flower and provide an alternative source of vegetable protein for the people of Rantau Kiri Village. This activity aims to provide knowledge and skills to the community in processing banana flower into delicious and nutritious shredded banana flower. The methods used in this training include socialization and education, demonstration, also hands-on practice of making shredded banana flower. The materials presented included an introduction to banana flower, its health benefits, processing techniques, and product marketing strategies. Demonstrations and hands-on training provided participants with the opportunity to observe and practice the process of making shredded banana flower. Evaluation results showed that the training successfully improved participants' knowledge and skills in making shredded banana flower. In addition, participants also showed high enthusiasm and interest in developing the business of making shredded banana heart as a local food product.